Influence of the photonic crystal medium on the self-interaction of electrons. (April 2015) - Gainutdinov, R Kh; Khamadeev, M A; Mohebbifar, M R; Petrova, A S; Ziyatdinova, K A; Salakhov, M Kh
Abstract: The self-interaction of an electron in the photonic crystal medium is investigated. We show that modification of the self-interaction of electrons in photonic crystals is very significant and, as a consequence, at some photon frequencies the electron-light interaction becomes effectively strong.